Arylcyanoacrylamides as inhibitors of the Dengue and West Nile virus proteases - Nitsche, Christoph; Steuer, Christian; Klein, Christian D. (Bioorganic & medicinal chemistry, 2011)
The 3-aryl-2-cyanoacrylamide scaffold was designed as core pharmacophore for inhibitors of the Dengue and West Nile virus serine proteases (NS2B-NS3). A total of 86 analogs was prepared to study the structure-activity relationships in detail. Thereby, it turned out that the electron density of the aryl moiety and the central double bond have a crucial influence on the activity of the compounds, whereas the influence of substituents of the amide residue is less relevant. The para-hydroxy substituted analog was found to be the most potent inhibitor in this series with a Ki-value of 35.7μM at the Dengue and 44.6μM at the West Nile virus protease. The aprotinin competition assay demonstrates a direct interaction of the inhibitor molecule with active centre of the Dengue virus protease. The target selectivity was studied in a counterscreen with thrombin and found to be 2.8:1 in favor of DEN protease and 2.3:1 in favor of WNV protease, respectively.